The practice of humanitarian work psychology. Issue 5 (28th October 2016) - Harry, Tinashe Timothy; Dodd, Nicole
Abstract : Humanitarian work psychology (HWP) seeks to improve the welfare of workers who provide a broad range of support to survivors of calamities both natural and man-made. It is an emerging interdisciplinary field of practice spanning expertise from many psychological fields to promote decent work and safe work conditions for those at the forefront of acute disasters of any kind. Personnel functions and health and safety issues are critical to humanitarian service roles. Research is needed to best inform the practice of humanitarian work in a globalised world culture, including strategies to support the well-being of individuals that are involved in humanitarian work.